Status Nutrisi Mineral Rusa Totol (Axis axis) di Lingkungan Istana Kepresidenan Bogor - Rahmita Yulia Andini; Suryahadi Suryahadi; Sri Suharti (Institut Pertanian Bogor, 2022)
The study aimed to determine the effect of mineral status (Ca, P, Fe, Mn, Zn, Cu, and Pb) in soil, grass, and hair of spotted deer in the Bogor Presidential Palace. Fifteen male deer were randomly selected with an age of ± 2.5‒6 years. Soil was collected from ten points representing land, and grass samples were obtained by sampling from several points of the grazing area. Mineral content in soil, grass, and deer hair were analyzed using the atomic absorption spectrophotometry. The results showed that the level of Ca (0.03%) and P (0.016%) in the soil are deficient, Mn (1960 ppm), Zn (33.89 ppm), and Cu (77.23 ppm) are considered in the normal range, and Fe and Pb elements are high. Mineral levels of Ca, P, Cu, and Zn in grasses do not meet the daily requirements, whilst high levels of Fe and Mn minerals exceed the requirements for the spotted deer. The Pb content in grass is 0.94 ppm, which is within the normal limit. The levels of Ca (0.02%), Fe (308.11 ppm). and Mn (6.18 ppm) minerals in deer hair are high, however, zinc (44.68 ppm) and Cu (3.08 ppm) levels are low. High Pb level (14.38 ppm) is due to the long-term impact of Pb accumulation. Keywords: Bogor Palace, mineral status, Axis axis